Strategi Pengembangan Program Desa Wisata Dalam Mewujudkan Desa Mandiri Di Dinas Pariwisata Dan Kebudayaan Kabupaten Kepulauan Selayar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
Development strategy is the plan of an organization or government in improving the Abstract Development strategy was the plan of an organization or government in improving the performance of quality human resources. This study aimed to find out the strategy of developing a tourism village program in realizing an independent village. This study used a qualitative descriptive type of research, to provide an overview of the tourism village program development strategy in realizing an independent village. The data analysis technique used data reduction, data presentation and conclusion. Then the data collection techniques used  observation, interviews and documentation studies. The results of the study showed that the strategy implemented had not shown maximum results, this was evidenced by the 4 indicators used as follows: (a) HR, tourism village managers who still needed training and coaching; (b) Funds, which were still lacking and had not been channeled directly for the development of existing tourism objects, especially in the lagoon beach tourism of Bontolebang village, which were still lacking in terms of infrastructure; (c) Information and technology, had made efforts to promote through print media, social media and had an official website; and (d) Infrastructure facilities were still lacking in carrying out their role as facilitators. Judging from the lack of available facilities, especially in the tourist village of Bontolebang.